Results of comprehensive studies conducted by the Central Research Institute (VNIIZhT) and construction work of the Ministry of Railways (RZD) to increase the loading gauge of freight and passenger rolling stock on the railways of Russian Federation - Yu. M. Lazarenko (Вестник Научно-исследовательского института железнодорожного транспорта, 2019)
The article presents the content and results of a set of studies on the scientific and methodological support for the modernization of structures and devices built according to the old loading gauge standards or its expired durability, the entire 1520 (1524) mm gauge railway network under the loading gauge standard T for rolling stock, allowing to increase axle and running loads of cars and due to this — the mass of trains, as well as solve the global problem that arose in the middle of the last century to increase the efficiency of the most important branch of Russia — railway transport. Variants of increased loading gauges were developed (Тпр for any rolling stock, Тц for tanks, Та — for electric rolling stock, Тб — for passenger cars), which were included in the GOST 9238 – 83 “Loading gauges of railway rolling stock and structure clearance” and Ministry of railways instructions (no. TsP/4425 — for clearance of structures; no. TsV/4422 — for loading gauge of the rolling stock and no. TsD/4172 — for transportation of oversized and heavy (nonstandard) freights), as well as zonal and flatcars loading gauges. Scientific and methodological studies carried out by the institute during the half-century period (mid-XX — early XXI) identified structures and devices that limit the use of rolling stock of loading standard T, its elimination during 1982 – 2005, as well as transition of industrial enterprises to the production of new freight and passenger cars of increased loading standards Тпр and Та, developed by the Institute. This identification was made on the basis of the overall classification of all railway infrastructure and access railroads of the former USSR. New regulatory framework for railway rolling stock loading gauges and structure clearance (GOST 9238 – 2013) was developed based on a global survey of actual dimensions of all structures and infrastructure devices of the 1520 (1524) mm gauge railways (area 1520). Railway Research Institute of the Ministry of Railway Transport (currently, JSC “VNIIZhT”) made scientific and methodological support for the modernization of infrastructure objects, exhausted its life span for the 100-year period of operation. Scientific and methodological support carried out by the Institute allowed the creation and operation of rolling stock with an increased loading gauge standard Тпр: for freight traffic — with increased running loads by 2 ton/m or more compared to European railways; for passenger traffic — more comfortable and 39 % more spacious double-deck compartment cars. Increasing the loading gauge of the rolling stock provides increased efficiency of rail transport by increasing productivity, reducing the required fleet of cars for the transportation of equal volumes as well as operating costs. At the same time achieved annual total economic effect amounts to 2,205 billion rubles. Introduction of the flatcar loading gauge contributes to the organization of transportation of heavy trucks by rail and, therefore, improve the environmental situation.